(untitled) (Progressive Agriculture, 2016)
This study was aimed to assess the present status of retail market of dried fishery products in Sadar Upazila, Sylhet, Bangladesh during the period of January to May, 2015. A survey questionnaire was developed, pre-tested and finally used for the collection of data from 21 fish retailers from 5 different markets. It was observed that the dried fish distribution chain from producers to consumers run through a number of intermediaries: wholesalers, paikers, local vendors and retailers. The number of retailer in the markets varied between 2 to 12. A total of 22 freshwater sun dried fish products were found in the different markets of which 17 were small in size and 5 were big sized that represented 77% and 23% of market share, respectively. The price variation of the selected fish products depends on markets, species, size, quality and availability of the dried fish. The price of small dried fish species varied from BDT 300-800 per kg. The price of Punti, Tengra, Taki and Guchi baim ranged between BDT 300-400, BDT 450-500, BDT 500-600 and BDT 700-800 per kg, respectively. It was found that the retailers usually sell their products within 5-7 days after collection from the aratdars and they do not use any preservatives or insecticides within this period. It was also found that a retailer usually sell up to 10 kg of dried fish products per day in a larger market whereas in a smaller market it was about 4 kg per day. Lack of capital, higher transport cost, inadequate storage facilities and unhygienic market place were the major constraints as claimed by the retailers. The constraints identified in this study could be solved by providing participatory training for the producers to produce good quality products, providing loan facilities to poor retailers, ensuring proper marketing facilities and introducing modern packaging techniques to increase the shelf life of dried fish products. Progressive Agriculture 27 (2): 235-241, 2016